2019
DOI: 10.1101/gr.242719.118
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-aware plasma cell-free DNA fragmentation analysis in open chromatin regions informs tissue of origin

Abstract: Cell-free DNA (cfDNA) in human plasma is a class of biomarkers with many current and potential future diagnostic applications. Recent studies have shown that cfDNA molecules are not randomly fragmented and possess information related to their tissues of origin. Pathologies causing death of cells from particular tissues result in perturbations in the relative distribution of DNA from the affected tissues. Such tissue-of-origin analysis is particularly useful in the development of liquid biopsies for cancer. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 57 publications
7
172
0
Order By: Relevance
“…We considered non-overlapping windows of 500 kb across the genome annotated using Given a non-random distribution of urine cfDNA fragments across the genome, we hypothesized that genome-wide fragmentation patterns and positioning in urine may be informative of tissue of origin. Based on differences observed in urine cfDNA fragment size in open and closed chromatin regions, we developed a computational approach for correlating fragment size differences between active and inactive genomic regions to DNase I hypersensitive sites (DHS) across 116 cell types and tissues (using a published dataset) [17][18][19] . For each individual sample, we calculated median fragment size within non-overlapping 500 kb windows for all autosomes and normalized all median values to z-scores.…”
Section: Resultsmentioning
confidence: 99%
“…We considered non-overlapping windows of 500 kb across the genome annotated using Given a non-random distribution of urine cfDNA fragments across the genome, we hypothesized that genome-wide fragmentation patterns and positioning in urine may be informative of tissue of origin. Based on differences observed in urine cfDNA fragment size in open and closed chromatin regions, we developed a computational approach for correlating fragment size differences between active and inactive genomic regions to DNase I hypersensitive sites (DHS) across 116 cell types and tissues (using a published dataset) [17][18][19] . For each individual sample, we calculated median fragment size within non-overlapping 500 kb windows for all autosomes and normalized all median values to z-scores.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, a recent work by Sun et al has demonstrated that another epigenetic biomarker, such as cfDNA fragmentation pattern, could also be informative for CV diagnosis besides the above-mentioned DNA methylation. 114 Owing to their reversibility, most attention should be given to circulating epigenetic-sensitive changes, which may provide innovative drug targets. In particular, individual DNA methylation profiles may be useful to identify a personalised dietary interventions consisting of consuming foods containing methyl donors to attenuate cardiac phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, pioneering researchers at the Li Ka Shing Institute of Health Sciences consolidated these understandings of fetal cfDNA in a publication that opens further opportunities for prenatal diagnosis, oncology, and transplant medicine. In this proof‐of‐principle study, the authors proposed a new method for nucleosome positioning profiling and quantitative determination of the relative contributions of various tissues in plasma DNA by fragmentation pattern analyses . In this elegant paper, the investigators capitalise on the knowledge that cfDNA fragmentation is not random but occurs in tissue‐specific patterns that reflect open chromatin regions and nucleosome position and is deducible by sequencing coverage patterns.…”
Section: Fragmentomicsmentioning
confidence: 99%
“…The approach used in this report was to first screen the pregnant mothers' germline DNA, and the cfDNA in maternal plasma is reflex tested in mothers subsequently identified as carriers to determine the fetal genotype. Much of the data reported in this paper comes from modelling experiments using spiked‐in genomic DNA, which may be a useful starting point for assay development but, as discussed above, we know that fetal cfDNA is different from maternal cfDNA or postnatal DNA . There appears to be a high inconclusive rate in this study, although the FF was reported at greater than 10% in most cases.…”
Section: Non‐invasive Prenatal Diagnosis and Screening For Monogenicmentioning
confidence: 99%